2020
DOI: 10.1021/acsami.0c11086
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Dielectric and Thermal Properties of Oxide Dielectrics via Substrate Biasing in Plasma-Enhanced Atomic Layer Deposition

Abstract: The ability to control the properties of dielectric thin films on demand is of fundamental interest in nanoscale devices. Here, we modulate plasma characteristics at the surface of a substrate to tune both dielectric constant and thermal conductivity of amorphous thin films grown using plasmaenhanced atomic layer deposition. Specifically, we apply a substrate bias ranging from 0 to ∼117 V and demonstrate the systematic tunability of various material parameters of Al 2 O 3 . As a function of the substrate bias,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…In figure 2(b), it can be seen that the mass density reaches its maximum at 5 W, and decreases when the substrate bias reaches 10 W and then becomes stable at higher power. These results are in good agreement with the studies reported by Kim et al [30], which show that the mass density reached a maximum (3.1 g cm −3 ) when biasing the substrate with an RF power source voltage at 20 V. The decrease of the mass density with ion bombardments has been attributed to the increase of the incorporation of impurities, such as carbon and hydrogen into the Al 2 O 3 film [28]. The hydrogen content is mostly contributed as OH groups in the film deposited by PEALD [28,32,33].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In figure 2(b), it can be seen that the mass density reaches its maximum at 5 W, and decreases when the substrate bias reaches 10 W and then becomes stable at higher power. These results are in good agreement with the studies reported by Kim et al [30], which show that the mass density reached a maximum (3.1 g cm −3 ) when biasing the substrate with an RF power source voltage at 20 V. The decrease of the mass density with ion bombardments has been attributed to the increase of the incorporation of impurities, such as carbon and hydrogen into the Al 2 O 3 film [28]. The hydrogen content is mostly contributed as OH groups in the film deposited by PEALD [28,32,33].…”
Section: Resultssupporting
confidence: 94%
“…They also found that the properties of SiN x films were degraded. Kim et al [30] have demonstrated the modulation of both dielectric and thermal characteristics of Al 2 O 3 thin films using substrate biasing in PEALD. In our previous work [31], we have shown that substrate biasing can be used for simultaneous tuning of film quality and dielectric properties of aluminium nitride (AlN) thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we discuss the influence of ions during PE-ALD. In several studies on PE-ALD of oxides as well as nitrides [186,[210][211][212][213][214][215][216][217][218], a significantly beneficial influence of ions has been reported, such as impurity removal, densification [219], and crystallization (illustrated in figure 11(C2)). On the other hand, unfavorable effects such as sputtering, amorphization, and impurity implantation (illustrated figure 11(C3)) can be present when the supplied ion energy or dose is too high [186,193].…”
Section: Reactionmentioning
confidence: 99%
“…Exciting progress has been made in the PEALD growth of oxides, such as ZrO 2 , HfO 2 , SiO 2 , TiO 2 , and Al 2 O 3 . Parameters including plasma composition, ion dose, and substrate bias were studied to improve the material and interface properties in electronic devices. PEALD-grown HfO 2 single-layer thin films, SiO 2 single-layer thin films, as well as HfO 2 and SiO 2 pairs for AR and high-reflective (HR) thin films have been studied specifically for laser applications.…”
Section: Introductionmentioning
confidence: 99%